Plasma combustion technology for micro gas turbine using Kuwaiti sheep fat biodiesel - Alrashidi, Ahmad M R N (2021)
The technology of using only fossil fuel in the operation of a gas turbine engine is facing issues that include low thermal efficiency, poor atomization, low vapour pressure, and high greenhouse gases (GHG). Thus the research motivation is to restructure the design principle of gas turbines for enhancing performance, fuel consumption reduction and GHG emission reduction of a gas turbine. Hence the main objective of this research is to investigate the impact assessment of the plasma combustion technology for a micro gas turbine (MGT) using biodiesel fuel. This is achieved through external integration of hybrid plasma-rich mixture injection at the compressor inlet of the engine system for enhanced combustion of biodiesel fuel through improved thermal efficiency by eight percent. In view of this, the specific objectives are (1) To fabricate, develop and assemble a mini gas turbine (MGT) engine system with an external integrated hybrid Plasma-Torch-Ultrasonic atomizer at the compressor inlet point of the 50kW (67hp) MGT engine in the laboratory. (2) To conduct characterization of Kuwaiti sheep fat biodiesel for the MGT engine operation. (3) To evaluate and validate the combustion performance of the fabricated MGT engine and GHG emission reduction. The methodology involved the design, fabricating and assembling of individual systems (turbo charger, compressor system, ignition system, ultrasound-assisted atomizing system, external integration of hybrid plasma-rich fuel injection at the compressor system, inlet air inlet, oil system, and control unit) for the 50 kW (67hp) MGT test bed in the laboratory. The MGT test bed was meticulously designed with an increase in distance between the inlet of the micro gas turbine engine and plasma torch nozzle and tested for stability with the expansion of the inlet to reduce the speed of air entry. This ensures repeatability, reliability, and accurate data acquisition through in-depth experimental design with output data of components consistent with literature thus fulfilling Objective 1 of this thesis. Secondly, fuel characterization (specific gravity, density, kinematic viscosity, total acid number, water content, total sulfur, flash point, lubricity, cloud point, pour point, calcium and magnesium content was according to the American Society for Testing and Materials (ASTM) standards for six fuels (kerosene, diesel, blends of Kuwaiti sheep fat biodiesel (B20, B50, B75 and B100) performed at the Petroleum Research Center, Kuwait Institute for Scientific Research. Results showed biodiesel has higher kinematic viscosity and density than diesel and kerosene; flash point (B75) closest to kerosene and acid number (B20) value 0.03206 mgKOH/gm in compliance to the ASTM D6751 and EN 14214 standard limits of 0.5 mgKOH/gm that indicates minimal nitrogen and sulphur emissions (less soot). These results show that blended biodiesel is suitable for MGT fuel thus Objective 2 of the thesis is achieved. The MGT engine's general performance for all loading conditions when operated under integrated plasma-rich fuel mixture injection with evaluated results (a) fuel consumption was generally 9% lower than normal conditions higher than pledged value of 1.5% (b) thrust value under normal condition is 1.7 - 4.2 kgf and 1.8 - 4.35 with plasma system (c) achieved average thermal efficiency for biodiesels 15 – 18% higher than 8% as pledged. (d) achieved GHG emissions on average 0.07% for CO; 3% for CO2; 5% for NO; and 10% for NO2. (e) B100 exhibits the highest compressor outlet temperature, highest compressor output pressure and best performance in fuel flow rate suggesting unique but desirable features of biodiesel fuel for MGT. Thus the efficacy of integrated plasma-rich fuel mixture assisted combustion operation is presented that fulfils Objective 3 of the thesis. Therefore, Alternative hypothesis H1 (μo ≠ μ1): Intake integration of hybrid plasma-rich fuel mixture at the compressor inlet of mini gas turbine (MGT) engine with assisted ultrasonic atomiser does improve engine performance and exhaust GHG emissions level control is accepted. The findings of this study can serve as a potential technology for improving the efficiency of fuel combustion and ignition in GT engines. It also presents an efficient way of using sustainable renewable sources of energy (animal fat biodiesel) as a means of reducing GHG emissions level.